Hadith #1344 - Sunan al-Nasa'i - Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Aisha bint Abi Bakr; Khalid bin Abi 'Imran خالد بن أبي عمران; Khlad bin Sulaiman al-Hdrmy خلاد بن سليمان الحضرمي; Mansur bin Salma bin 'Abdul 'Aziz منصور بن سلمة بن عبد العزيز; Muhammad bin Ishaq al-Saghani محمد بن إسحاق الصغاني; Urwa ibn al-Zubayr عروة بن الزبير (Sunan al-Nasa'i)
“Al-Mughirah bin Shu’bah wrote to Mu’awiyah (Saying) that the Messenger of Allah (ﷺ) used to say following every prayer, after the taslim: ‘La Ilaha Illallah wahdahu la sharika lah, lahul-mulk wa lahul-hamd wa huwa ‘ala kulli shay’in qadir. Allahumma la mani’ lima a’taita wa la mu’tia lima mana’ta wa la yanfa’u dhal-jaddi minka al-jadd. (There is none worthy of worship except Allah (ﷺ) alone with no partner or associate. He is the Dominion and to Him be all praise, and
Grade:

Hadith #1533 - Sunan al-Nasa'i - Abu Bakr bin Abi al-Jhm أبو بكر بن أبي الجهم بن صخير العد; ibn Abbas; Muhammad bin Bashar Bindar محمد بن بشار بندار; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Ubaydullah bin 'Abdullah bin 'Utba عبيد الله بن عبد الله بن عتبة بن مسعود; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan al-Nasa'i)
“There was a drought during the time of the Messenger of Allah (ﷺ). While the Messenger of Allah (ﷺ) was giving the Khutbah on the minbar one Friday, a Bedouin stood up and said: ‘O Messenger of Allah wealth has been destroyed and our children are hungry; pray to Allah for us.’ The Messenger of Allah (ﷺ) raised his hands, and we could not see even a wisp of a cloud in the sky, but by the One in Whose hand is my soul, he did not lower (his hands) before clouds like mountains appeared,
Grade:

Hadith #1861 - Sunan al-Nasa'i - Amr bin 'Ali bin Bahr al-Bahli عمرو بن علي بن بحر الباهلي; Awf bin Abi Jamila al-A'rabi عوف بن أبي جميلة الأعرابي; Safwan bin Mhrz bin Ziyad صفوان بن محرز بن زياد المازني; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Sulaiman bin Harb سليمان بن حرب (Sunan al-Nasa'i)
, when she was told that Ibn ‘Umar said that the deceased is punished due to the weeping of the living for him, ‘Aishah said: “May Allah forgive Abu ‘Abdur-Rahman; he is not lying, but he has forgotten or made a mistake. The Messenger of Allah passed by a (deceased) Jewish woman for whom people were weeping and he said: ‘They are weeping for her and she is being punished.”‘
Grade:

Hadith #2315 - Sunan al-Nasa'i - Abdullah bin Swad'h عبد الله بن سوادة; Amr bin Mnswr al-Nsa'iy عمرو بن منصور النسائي أبو سعيد; Anas ibn Malik; Muslim bin Ibrahim al-Azdy مسلم بن إبراهيم الأزدي الفراهيدي; Wahayb bin Khalid bin 'Ajlan al-Bahli وهيب بن خالد بن عجلان الباهلي (Sunan al-Nasa'i)
“We were traveling with the Prophet and among us were some who were fasting and some who were not criticize those who were not, and those who were not fasting did not criticize those who were.”
Grade:

Hadith #4573 - Sunan al-Nasa'i - al-Laith bin Sa'd الليث بن سعد; Fadala bin 'Ubaid bin Naqid; Hnsh bin 'Abdullah حنش بن عبد الله ويقال; Khalid bin Abi 'Imran خالد بن أبي عمران; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Sa'id bin Yazid al-Humayri سعيد بن يزيد الحميري القتباني (Sunan al-Nasa'i)
“O people, you have invented kinds of transactions, I do not know what they are, but make sure it is gold for gold, of the same weight, or silver for silver, of the same weight. There is nothing wrong with selling silver for gold, hand to hand, giving more silver than gold, but no credit is allowed. When you sell wheat for wheat and barley for barley, it should be measure for measure, but there is nothing wrong with selling barley for wheat, hand to hand, giving more barley than wheat, but no
Grade:

Hadith #4574 - Sunan al-Nasa'i - al-Laith bin Sa'd الليث بن سعد; Amr bin Mnswr al-Nsa'iy عمرو بن منصور النسائي أبو سعيد; Fadala bin 'Ubaid bin Naqid; Hashaym bin Bashayr bin al-Qasim هشيم بن بشير بن القاسم; Hnsh bin 'Abdullah حنش بن عبد الله ويقال; Khalid bin Abi 'Imran خالد بن أبي عمران; Muhammad bin Mhbwb al-Binany محمد بن محبوب البناني (Sunan al-Nasa'i)
“The messenger of Allah said: ‘Gold for gold, of equal measure; silver for silver, of equal measure; salt for salt, dates for dates wheat for wheat, barley for barley, like for like. Whoever gives more or takes more has engaged in Riba.”‘ (Sahih) The wording is that of Muhammad Yaqub did not mention – “Wheat for wheat”.
Grade:

Hadith #2345 - Sunan Abi Dawud - Abdullah bin Swad'h عبد الله بن سوادة; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Samra bin Jundub (Sunan Abi Dawud)
The Prophet (ﷺ) as saying: How good is the believers meal of dates shortly before dawn.
Grade: Sahih

Hadith #3350 - Sunan Abi Dawud - Abdullah bin Mubarak عبد الله بن المبارك; Fadala bin 'Ubaid bin Naqid; Hnsh bin al-Ma'tmr حنش بن المعتمر; Khalid bin Abi 'Imran خالد بن أبي عمران; Muhammad bin 'Isa bin Hyan محمد بن عيسى بن حيان (Sunan Abi Dawud)
“He said: If these classes differ, sell as you wish if payment is made on the spot.”
Grade: Sahih

Hadith #3351 - Sunan Abi Dawud - al-Laith bin Sa'd الليث بن سعد; Fadala bin 'Ubaid bin Naqid; Hnsh bin 'Abdullah حنش بن عبد الله ويقال; Khalid bin Abi 'Imran خالد بن أبي عمران; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Sa'id bin Yazid al-Humayri سعيد بن يزيد الحميري القتباني (Sunan Abi Dawud)
The Prophet (ﷺ) was brought a necklace in which there were gold and pearls. (The narrators AbuBakr and (Ahmad) Ibn Mani’ said: The pearls were set with gold in it, and a man bought it for nine or seven dinars.) The Prophet (ﷺ) said: (It must not be sold) till the contents are considered separately. The narrator said: He returned it till the contents were considered separately. The narrator Ibn Asa said: By this I intended trade. Abu Dawud said: The word hijarah (stone) was recorded in his
Grade: Sahih

Hadith #3540 - Sunan Abi Dawud - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Abu Umama bin Sahl; Ahmed bin 'Amr bin al-Sarh أحمد بن عمرو بن السرح أبو الطاهر; al-Qasim ibn Muhammad القاسم بن محمد بن أبي بكر الصديق; Khalid bin Abi 'Imran خالد بن أبي عمران; Ubaidullah bin Abi Ja'far عبيد الله بن أبي جعفر المصري (Sunan Abi Dawud)
The Prophet (ﷺ) said: The similitude of the one who takes back what he gifted is like that of a dog which vomits and then it eats vomit. When a donor seeks to take back (his gift), it should be made known and he informed why he sought to take it back. Then whatever he donated should be returned to him.
Grade: Hasan Sahih

Hadith #3979 - Sunan Abi Dawud - Aslm al-Mnqry Abu Sa'id Hdythh أسلم المنقري; ibn Umar; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Ubayy ibn Ka'b (Sunan Abi Dawud)
The Prophet (ﷺ) read the verse mentioned above, “min du’f.”
Grade: Hasan

Hadith #4263 - Sunan Abi Dawud - Abdul Malik bin Shu'aib bin al-Laith عبد الملك بن شعيب بن الليث بن سعد; Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Abdur Rahman bin Harmaz al-A'araj عبد الرحمن بن هرمز الأعرج أبو داود; Abu Hurairah; al-Laith bin Sa'd الليث بن سعد; Khalid bin Abi 'Imran خالد بن أبي عمران; Yahya bin Sa'id al-Ansari يحيى بن سعيد الأنصاري (Sunan Abi Dawud)
I swear by Allah, I heard the Messenger of Allah (ﷺ) say: The happy man is he who avoids dissensions: happy is the man who avoids dissensions; happy is the man who avoids dissensions: but how fine is the man who is afflicted and shows endurance.
Grade: Sahih

Hadith #5161 - Sunan Abi Dawud - Baqiyya bin al-Walid bin Sa'aid بقية بن الوليد بن صائد; Muhammad bin Khalid bin Rafa'i محمد بن خالد بن رافع; Uthman bin Zufar bin Muzaham عثمان بن زفر بن مزاحم (Sunan Abi Dawud)
The Prophet (ﷺ) said: Feed those of your slaves who please you from what you eat and clothe them with what you clothe yourselves, but sell those who do not please you and do not punish Allah’s creatures.
Grade: Sahih

Hadith #715 - Jami' al-Tirmidhi - Abdullah bin Swad'h عبد الله بن سوادة; Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Anas ibn Malik; Muhammad bin Sulaym محمد بن سليم أبو هلال الراسبي; Waki' bin al-Jarrah وكيع بن الجراح; Yusuf bin 'Isa bin Dinar يوسف بن عيسى بن دينار الزهري (Jami' al-Tirmidhi)
“Some cavalry man of the Messenger of Allah came galloping upon us, so I came to the Messenger of Allah and found him having lunch. He said: “Come and eat.” I said: ‘I am fasting.’ So he said: ‘Come and I will narrate to you about the fast – or fasting. Indeed Allah Most High lifted (the fast and) half of the Salat from the traveler, and (He lifted) the fast – or fasting – from the pregnant person, or the breast-feeding person.’ And by Allah! The Prophet said both of them or
Grade:

Hadith #1133 - Jami' al-Tirmidhi - Abu Bakr bin Abi al-Jhm أبو بكر بن أبي الجهم بن صخير العد; Abu Da'ud أبو داود السجستاني الأزدي; Mahmud bin Ghaylan محمود بن غيلان العدوي مولاهم أبو أحمد; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Jami' al-Tirmidhi)
“We got some captives on the day of Awtas, and they had husbands among their peopled. They mentioned that to the Messenger of Allah, so the following was revealed: And women who are already married, except those whom your right hands posses.
Grade:

Hadith #1251 - Jami' al-Tirmidhi - al-Laith bin Sa'd الليث بن سعد; Fadala bin 'Ubaid bin Naqid; Hnsh bin 'Abdullah حنش بن عبد الله ويقال; Khalid bin Abi 'Imran خالد بن أبي عمران; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Sa'id bin Yazid al-Humayri سعيد بن يزيد الحميري القتباني (Jami' al-Tirmidhi)
From his father, from his grandfather, that the Messenger of Allah (ﷺ) said: “Both the buyer and the seller retain the option as long as they did not separate, unless they agreed to making it optional. And it is not lawful for him to separate from his companion, fearing that he will change his mind.” This Hadith is Hasan and this means separating from him after the sale, fearing that he will change his mind. And if the separation referred to speech, and there was no option left for him af
Grade:

Hadith #188 - Sunan Ibn Majah - Hameed bin Musa'da bin al-Mubarak حميد بن مسعدة بن المبارك; Khalid bin al-Harith bin 'Ubaid خالد بن الحارث بن عبيد; Qatada قتادة; Sa'id bin Abi Sa'id; Safwan bin Mhrz bin Ziyad صفوان بن محرز بن زياد المازني (Sunan Ibn Majah)
“I heard the Messenger of Allah say: ‘Woe to the Achilles’ tendon because of Hell-fire.”
Grade:

Hadith #1706 - Sunan Ibn Majah - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Abu al-Darda; Amr bin al-Harith bin Ya'qub عمرو بن الحارث; Amr bin Sawad عمرو بن سواد; Sa'id bin Abi Hilal سعيد بن أبي هلال الليثي; Zayd bin Aymn زيد بن أيمن (Sunan Ibn Majah)
that when Saudah bint Zam’ah grew old, she gave her day to ‘Aishah, and the Messenger of Allah went to ‘Aishah on Saudah’s day.
Grade:

Hadith #1736 - Sunan Ibn Majah - Abdullah bin Swad'h عبد الله بن سوادة; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Ali bin Muhammad bin Ishaq al-Tanafasi علي بن محمد بن إسحاق الطنافسي; Anas ibn Malik; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Ibn Majah)
“A man from Banu Fazdrah came to the Messenger of Allah, and said: ‘O Messenger of Allah, my wife has given birth to a black boy! The Messenger of Allah said: ‘Do you have camels?’ He said: ‘Yes.’ He said: ‘What color are they?’ He said: ‘Red.’ He said: ‘Are there any grey ones among them?’ He said: ‘Yes, there are some grey ones among them.’ He said: ‘Where does that come from?’ He said: ‘Perhaps it is hereditary.’ He said: ‘Likewise, perhaps this is heredi
Grade:

Hadith #3422 - Sunan Ibn Majah - Abdullah bin Swad'h عبد الله بن سوادة; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Ali bin Muhammad bin Ishaq al-Tanafasi علي بن محمد بن إسحاق الطنافسي; Anas ibn Malik; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Ibn Majah)
“Allah is Gentle and loves gentleness, and He grants reward for it that He does not grant for harshness.”
Grade: